Editorial - Ezzeddine, Petra; Havelková, Hana (Lidé města, 2016)
Our original aim in preparing this monothematic issue was to focus on a “blank spot” in migration studies – the issue of ageing in the process of migration. This is an area that has long remained empirically unresearched. In the field of migration studies, academic interest has focused more on the connection between migration and the ageing of the recipient societies (demographic studies) and the influence of migration on the ageing of the population in the country of origin, in other words on situations where those migrating are mostly of productive age. A further issue that arises during study of the connection between gender, ageing and migration is the field of care practices. This in the end proved to be the thematic axis of all the studies included in our monothematic issue. In this issue of Urban People we present selected empirical studies from the field of social anthropology and sociology. They use qualitative data from surveys of male and female migrants concerning, from various perspectives, the theme of old age.